Comparing the efficacy and selectivity of Ck2 inhibitors: a phosphoproteomics approach - Borgo, Christian; Cesaro, Luca; Hirota, Tsuyoshi; Kuwata, Keiko; D’Amore, Claudio; Ruppert, Thomas; Blatnik, Renata; Salvi, Mauro; Pinna, Lorenzo A. (European journal of medicinal chemistry, 2021)
CK2 (an acronym derived from the misnomer “casein kinase 2”) denotes a ubiquitous, highly pleiotropic protein kinase which has been implicated in global human pathologies, with special reference to cancer. A large spectrum of fairly selective, cell permeable CK2 inhibitors are available, one of which, CX4945 is already in clinical trials for the treatment of neoplasia. Another recently developed CK2 inhibitor, GO289, displays in vitro potency and selectivity comparable to CX4945. Here the cellular efficiency of these two inhibitors has been evaluated by treating C2C12 myoblasts for 5 h with each of them at 4 μM concentration and running a quantitative phosphoproteomics analysis of phosphosites affected by the two compounds. A small but significant proportion of the quantified phosphosites is decreased by treatment with CX4945 and, even more with GO289. This figure substantially increases if a subset of quantified phosphosites conforming to the CK2 consensus (pS/pT-x-x-D/E/pS/pT) is considered. Also in this case GO289 is more effective than CX4945. By adopting stringent criteria two shortlists of 70 and 35 sites whose phosphorylation is decreased >50% by GO289 and CX4945, respectively, have been generated. All these phosphosites conform to the consensus of CK2 with just sporadic exceptions. Their WebLogos are indistinguishable from that of bona fide CK2 phosphosites and their Two-Sample Logos rule out any significant contribution of Pro-directed and basophilic protein kinases to their generation. To sum up, we can conclude that by treating C2C12 cells for 5 h with either CX4945 or GO289 off-target effects are negligible since almost all the phosphosites undergoing a substantial reduction are attributable to CK2, with a higher inhibitory efficacy displayed by GO289. CX4945 and GO289 provide highly selective tools to control the CK2-dependent phosphoproteome compared with previously developed CK2 inhibitors.
Gesehen am 21.06.2021